The ins and outs of top income mobility - Rolf Aaberge; Anthony B. Atkinson; Jørgen Modalsli (Statistics Norway, Research Department, 2013)
This paper is concerned with the question of whether top income earners are permanently there or only temporarily receive the highest incomes. How much mobility is there at the top of the income distribution, and how has mobility changed over time? The paper makes both a methodological and an empirical contribution to answering these questions. The first part of the paper introduces a family of top income mobility measures based on differences in average annual incomes of top income earners in short-term and long-term distributions of income. Norwegian income tax records are then employed to study top income mobility in Norway since 1967. The results reveal low levels of top income mobility, but a relatively large increase in mobility starting at the same time as the income shares of the top income receivers started to increase around 1990.
Keywords: J31; E24; D63; N34; 330; Top income shares; Income mobility; Inequality